Smad1 Promotes Tumorigenicity and Chemoresistance of Glioblastoma by Sequestering p300 From p53 - Lingli Gong; Daxing Xu; Kaixiang Ni; Jie Li; Wei Mao; Bo Zhang; Zhening Pu; Xiangming Fang; Ying Yin; Li Ji; Jingjing Wang; Yaling Hu; et al. (Advanced Science)
Abstract Acetylation is critically required for p53 activation, though it remains poorly understood how p53 acetylation is regulated in glioblastoma (GBM). This study reveals that p53 acetylation is a favorable prognostic marker for GBM, regardless of p53 status, and that Smad1, a key negative regulator of p53 acetylation, is involved in this process. Smad1 forms a complex with p53 and p300, inhibiting p300's interaction with p53 and leading to reduced p53 acetylation and increased Smad1 acetylation in GBM. This results in enhanced tumor growth and resistance to chemotherapy, particularly in tumors with missense mutant p53. Acetylation of K373 is found to be essential for Smad1's oncogenic function but does not confer chemoresistance in the absence of p53. Through molecular docking, it is discovered that Smad1 and p53 both interact with the acetyltransferase domain of p300, but at different amino acid sites. Disturbing the interface of Smad1 through amino acid mutations abolishes the Smad1‐p300 complex and promotes p53 acetylation. Therefore, a small molecule is identified through virtual screening that specifically disrupts the Smad1‐p300 interaction, offering a promising strategy for inhibiting GBM and increasing chemosensitivity by inhibiting Smad1 acetylation and restoring p53 acetylation.